2016
DOI: 10.1261/rna.053561.115
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic long noncoding RNAs are frequently bound to and degraded at ribosomes in human cells

Abstract: Recent footprinting studies have made the surprising observation that long noncoding RNAs (lncRNAs) physically interact with ribosomes. However, these findings remain controversial, and the overall proportion of cytoplasmic lncRNAs involved is unknown. Here we make a global, absolute estimate of the cytoplasmic and ribosome-associated population of stringently filtered lncRNAs in a human cell line using polysome profiling coupled to spike-in normalized microarray analysis. Fifty-four percent of expressed lncRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
177
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(196 citation statements)
references
References 65 publications
(80 reference statements)
10
177
1
Order By: Relevance
“…This hypothesis is supported by a clear correlation between the number of possible ORFs on these transcripts and the likelihood of being subject to NMD (Fig. 4B) and by the fact that recent ribosome profiling studies and polysome analyses found many noncoding RNAs to be associated with ribosomes (Ingolia et al 2011(Ingolia et al , 2014Carlevaro-Fita et al 2016).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…This hypothesis is supported by a clear correlation between the number of possible ORFs on these transcripts and the likelihood of being subject to NMD (Fig. 4B) and by the fact that recent ribosome profiling studies and polysome analyses found many noncoding RNAs to be associated with ribosomes (Ingolia et al 2011(Ingolia et al , 2014Carlevaro-Fita et al 2016).…”
Section: Discussionmentioning
confidence: 65%
“…Given that NMD is a translation-dependent process, it might be surprising at first sight that several genes annotated as "noncoding" are affected. However, many pseudogenes are known to give rise to PTC-containing mRNAs (Mitrovich and Anderson 2005) and recent ribosome profiling studies found many transcripts categorized as lincRNAs to be associated with ribosomes (Ingolia et al 2011;Calviello et al 2015;Carlevaro-Fita et al 2016). In a few cases, the short polypeptides encoded by these lincRNAs were even detected (Ingolia et al 2014) thus revealing them as a misnomer.…”
Section: Identification Of Nmd-targeted Transcriptsmentioning
confidence: 99%
“…In contrast, Carlevaro-Fita et al. [37] have recently shown that ribosomes are the default destination of most cytoplasmic lncRNAs and may play a role in their degradation because blocking ribosomal elongation results in the stabilization of many associated lncRNAs, which may be also the case for the GUT15 lncRNA. In 1995, Taylor and coworkers found that the level of the shorter GUT15 transcript was significantly increased in an actinomycin D (inhibitor of RNAPII transcription)- and cycloheximide (translational inhibitor)-treated tobacco cell line [15].…”
Section: Discussionmentioning
confidence: 99%
“…This translation is similar to that occurring at 5′ UTRs, and the vast majority of peptides produced by such translation events in lncRNAs and 5′ UTRs are likely to be immediately degraded and nonfunctional [as discussed at length by Housman and Ulitsky (2015)]. The presence of some ribosomeprotected fragments overlapping an lncRNA, or its localization to the polysome fraction (Carlevaro-Fita et al, 2016;van Heesch et al, 2014), do not, therefore, invalidate the noncoding nature of a transcript.…”
Section: The Identification and Annotation Of Lncrnasmentioning
confidence: 99%